Governança corporativa e competição : influências sobre a qualidade da informação contábil - Bastianello, Ricardo Furieri (2012)
This dissertation analyzes the quality of accounting information (QAI) on the interaction between corporate governance and competition, aiming to tackle questions that have not been addressed by the literature available so far, especially when it comes to comparing the four possible environments resulting of the combination between different competition and governance environments. When it comes to the relationship between competition and governance, studies such as Karuna s (2010) point out to the existence of a cause/effect relationship between the intensity of the competition and stronger governance. When discussing accounting and competition, Dhaliwal et al. (2008) evidenced a positive relation between the amount of competition and the conditional conservatism, which is considered one of the main priorities of accounting information. Thus, in what concerns the relationship between governance and accounting, findings made by Bushman et al (2000) confirm that accountancy has an influence on corporate governance. Ball et al (2000) are contrary to that opinion, claiming that it is corporate governance that impacts on accountancy, which means that the governance mechanisms present at a certain environment would play a fundamental role in the quality of accounting information. The product market competition was calculated using the Herfindahl Index and the identification of firms with strong or weak governance was based on BM&FBovespa listings, where firms listed in New Market or Level 2 were considered with strong governance, and the others were considered with weak governance. The data used was collected between 2000 and 2011, from the firms listed on the São Paulo Stock Exchange. The type of statistical analysis used to process data was the multiple regression with unbalanced panel data. In general, the results point to the same direction as previous ones, showing that both the presence of a strong governance and a highly competitive environment can enhance the accounting numbers in order to make them more qualitative. Interestingly, results suggest that in environments classified as uncompetitive and weak governance mechanisms, the quality of accounting information disclosed was relatively high, according to two of the three properties of the quality of accounting information analyzed